New methodology for pH measurements in fuel ethanol using glass electrode - Da Silva, Ricardo Moutinho [UNESP]; Borges, Paulo Paschoal; Serta Fraga, Isabel Cristina; Stradiotto, Nelson Ramos [UNESP] (ASTM International, 2011)
Studies carried out with glass electrode in anhydrous ethanol and ethanol-water solutions for measuring pH values have shown that this parameter depends on the solution composition, the contact time with the solution, the utilized temperature, and the type of electrolyte used. It was also observed that the glass electrode behavior in an acid medium differs from an alkaline medium. These studies provided correction factors for pH values from 2 to 12, allowing the realization of proper measurements of the hydrogen ionic activity in the ethanol-water and anhydrous ethanol solutions. However, these correction factors could not be applied to the fuel ethanol. Alternatively, a new method was developed for the correction of the pH values, which can be applied in hydrous and anhydrous fuel ethanol samples. Copyright © 2011 by ASTM International.
Keywords: Ethanol-water solutions; Fuel ethanol; Glass electrode; pH; Acid medium; Alkaline medium; Anhydrous ethanol; Contact time; Correction factors; Ethanol-water; Glass electrodes; Ionic activity; Measuring pH; PH measurements; pH value; Solution composition; Electrodes; Fuels; Glass; pH effects; Ethanol